CogLaboration Experiment 6, Force sensor object transfers - Koene, Ansgar (Dryad, 2013)
Data from Satoshi Endo's experiment on object transfer between two
subjects. The object was a force sensor and acceleration outfitted object
(see EuroHaptics 2012, Part I, LNCS 7282, pp. 103–111, 2012). Manipulation
consisted of having one or both subjects using their preferred or
non-preffered hand and/or with one or the other subject having their eyes
closed.
Keywords: grip force; human; Manual grasping; Object transfer